Prevalence of multimorbidity and its relationship with socioeconomic status among Chinese older adults over time - Qin Liu; Jiehua Lu (PLoS ONE, 2025)
Previous studies linking socioeconomic status (SES) to chronic diseases tended to focus on a single disease. As people age, they are more likely to suffer from multiple coexisting chronic conditions, known as multimorbidity. The study of multimorbidity is one of the key links to understanding the impact of population ageing from a comprehensive perspective. This study used four waves of cross-sectional data from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2018 to explore the prevalence of multimorbidity and its relationship with socioeconomic status among older adults in China over time. Participants aged 60 and older were selected for analysis. Both the Logistic Regression Model and the Negative Binomial Regression Model were adopted to examine the relationship between socioeconomic status and multimorbidity. The results showed that the prevalence of multimorbidity among older adults in China demonstrated an increasing trend over the years, from 46.16% in 2011 to 57.50% in 2018. A significant association was detected between socioeconomic status and multimorbidity among older adults, which was manifested as the higher the socioeconomic status, the greater the likelihood of being multimorbid. However, the relationship between the two has been changing over time, with the influence of SES on multimorbidity gradually disappearing and then reappearing in the opposite direction. Multimorbidity has become a critical health issue that should not be ignored for older adults in China, and the relationship between socioeconomic status and multimorbidity may be changing over time, which needs to be further explored with data over a longer period of time.